(3LOhd Ydi Hf MSf GdCchYs - (3Ydj Hf MSf GdGchYs
(3ChdgG (B:s
(3hHYO aEfgG deG XgQJ di bhGYO GdLOhd QZHJ Gf GLYd LOhdgG ef GdSfI GdChdi s
(3BNQgG (B:s
(3jfJgi HQSe gfOSi adci s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3jTJed Ydi LOGhd hQSheGJ adcjIs
(3eUOQ GbJfGA GdCUd (B:s
(3GdGeHQhRjGfG (B(252 D) s
Keywords: (3Gdadcs